Pengaruh Kepemimpinan terhadap Kinerja Karyawan pada PT. Perkebunan Nusantara VI Jambi - Selvi, Selvi; Ubaidillah, Ubaidillah; Syukri, Muhammad; Iskandar, Fadil (Dinasti Review Publisher, 2024)
Employee performance includes the quality and quantity of output as well as reliability at work. Employees can work well if they have high performance so they can produce good work too. With high employee performance, it is hoped that organizational goals can be achieved. On the other hand, organizational goals will be difficult or even unattainable if the employees do not have good performance so they cannot produce good work. This research aims to determine the description of leadership and employee performance, as well as to determine the influence of leadership on employee performance at PTPN VI Jambi. The research method used in this research is descriptive and quantitative methods. In this research, the population is all employees at PT. Perkebunan Nusantara VI Jambi. In this research, the sampling method was simple random sampling, so the research sample consisted of 74 respondents. The research results are shown by the results of the t test producing a significance value of 0.000, which means the significance value is less than 0.05, which means leadership at PT. Perkebunan Nusantara VI Jambi influences employee performance. So the R Square value is 0.446 or 44.6%. This means that the independent variable (leadership) has an effect on the dependent variable (employee performance) by 44.6. Based on the research that has been conducted, it can be concluded that leadership at PT. Perkebunan Nusantara VI Jambi shows the high category with a score of 301.5. Meanwhile, employee performance at PT. Perkebunan Nusantara VI Jambi was proven to be in the very high category with a score of 311. Then leadership had a significant positive effect on employee performance by 44.6% at PT. Perkebunan Nusantara VI Jambi.